Exploring the relationship between structure and activity in BODIPYs designed for antimicrobial phototherapy - Senge, Mathias (My University, 2020)
A synthetic strategy to BODIPY dyes is presented giving access to a range of new compounds relevant in the context of antimicrobial photodynamic therapy (aPDT). BODIPYs with the 8-(4-fluoro-3-nitrophenyl) and the 8-pentafluorophenyl substituents were used for the synthesis of new mono- and dibrominated BODIPYs. The para-fluorine atoms in these electron-withdrawing groups facilitate functional modification via nucleophilic aromatic substitution (SNAr) with a number of amines and thio-carbohydrates. Subsequently, the antibacterial phototoxic activity of these BODIPYs has been assessed in bacterial assays against the Gram-positive germ S. aureus and also against the Gram-negative germ P. aeruginosa. The bacterial assays allowed to identify substitution patterns which ensured antibacterial activity not only in phosphate-buffered saline (PBS) but also in the presence of serum, hereby more realistically modelling the complex biological environment that is present in clinical applications.
Keywords: thio-carbohydrates; BODIPYs; antimicrobial photodynamic therapy (aPDT); thio-carbohydrates; BODIPYs; antimicrobial photodynamic therapy (aPDT)